REPRESENTASI PERAN IBU SINGLE PARENT DALAM AKUN INSTAGRAM AYU TINGTING (@ayutingting92) - Raden Ayu Novaristin Hakiki (Prodi Ilmu Komunikasi FISIP Universitas Langlangbuana, 2019)
Instagram is one social media to express themselves as well as the media for the exchange of information. With Instagram, single parent mother can freely express her activities with her child. It is seen from celebrity Ayu TingTing (@ayutingting92) who participate and share their daily activities so that she has the most followers all over Indonesia. By making herself have the most followers make writers want to know how Ayu represents the role of single parent mother in educating and protecting her child. The author analyzes through candid photographs of Ayu TingTing with her daughter who goes into educational and protective classification using Charles Sanders Pierce's semiotics and divides them into icons, indexes, symbols. To strengthen photo analysis the author uses non verbal communication theory and interpersonal. The results showed that Ayu TingTing represented the educating role with the fun of playing while learning where she was the teacher for her daughter. While in the role of protecting, Ayu represent it with a touch to keep her child's health and keep from accident.